EDUKASI ANTI-NARKOBA BAGI SISWA SEBAGAI UPAYA PENCEGAHAN DINI DI LINGKUNGAN SEKOLAH - Fadlun Al-munzir; Fadilanurulain A.U; Rahma Nia; Bahtiar Tamrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Drug abuse is a serious threat to the younger generation, particularly students, because it has negative impacts on their health, psychology, academic achievement, and future; therefore, early prevention efforts in schools are a strategic step to protect students from such influences. This activity aimed to improve students’ understanding, awareness, and skills in rejecting drug abuse. The implementation method used an educational- participatory approach involving students of Pondok Pesantren Al-Ittihad DDI Soni in grades 10–12. The stages of the activity included interactive lectures, group discussions, role-play simulations, educational games, as well as evaluation and reflection. The results showed a significant increase in students’ knowledge of the types of drugs and their impacts, their courage to resist negative influences, and the growth of empathy and solidarity among peers. These findings demonstrate that the educational-participatory approach is effective in fostering critical awareness, social skills, and anti-drug attitudes among students. Academically, this activity contributes as an empirical model of school- based drug abuse prevention, while practically it can serve as a reference for other schools to develop similar sustainable programs.